PENGARUH GREEN INVESTMENT, KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Indriani, Meylina; Purwasih, Desy (LPPM Universitas Bina Bangsa, 2025)
This study aims to provide emprical evidence on the influence of green investment, finansial performance, and firm size on firm value. This study uses secondary data obtained from the official website of the Indonesia Stock Exchange and from the websites of each company in the SRI-KEHATI indeks listed on the IDX for the period from 2019 to 2023. The sample selection was carried out using the purposive sampling method based on specific criteria that align with the research needs. From the selection results, 11 companies were obtained with a total of 55 sample observations. The hyphotesist test in this research was conducted using Eviews 12 software. The results of the data analysis show that, simultaneously, green investment, profitability, leverage, and company siza have an impact on the company’s value. Meanwhile, the partial analysis reveals that profitability, leverage, and company size have an influence on the company’s vale, while green investment does not show a significant impact on the company’s value when tested individually.